Analisa Unsur Hara dan Uji Swot Pupuk Organik Dari Limbah Kepala Lele: Analisa Unsur Hara dan Uji Swot Pupuk Organik Dari Limbah Kepala Lele - Endro Puji Astoko; Nunuk Helilusiatiningsih (JURNAL ILMIAH AGRINECA, 2026)
The catfish farming industry uses a significant amount of water for its production processes, resulting in significant waste production. Catfish are a type of freshwater fish highly sought after by Indonesians. Catfish waste often causes problems due to its foul odor due to contamination with the environment, which is rich in putrefying microbes. The research location was the Laboratory in collaboration with the P3GI Laboratory in Kediri Regency. The research method used AAS ang SWOT analysis. The test samples used liquid organic fertilizer and solid fertilizer produced from the process of making fertilizer from catfish head and offal waste. The results of the study are as follows: the main macronutrients of the POC from catfish head waste are Nitrogen (N) at an average of 1.37%, Phosphorus (P) at 2.40%. Potassium (K) content at 3.90%, and Organic Carbon at 0.52%. Solid catfish head waste fertilizer contains 4.5% nitrogen (N), 6.80% phosphorus (PO4), and 4.70% potassium (K). Organic carbon (C) is 31%. Therefore, the nutrient analysis results for the organic fertilizer production process from catfish head waste show that the solid organic catfish waste fertilizer has the highest nutrient content, which is very good for plants. SWOT analysis is very important to carry out to make it easier to produce safe, reliable and good quality fertilizer.